HPLC assay for aflatoxins in dried red peppers and feedstuffs in Turkey - (:unkn) unknown (My University, 2002)
The purpose of this study was to investigate aflatoxins (AFs) B1, B2, G1 and G2 in contaminated dried red peppers and feedstuffs consumed in Turkey. The AFs were detected using high performance liquid chromatography (HPLC) and the results higher than 1 ppb were further confirmed by thin layer chromatography (TLC). In HPLC, the detection limit of B1 and G1 was 0.075 ng and for B2 and G2 it was 0.060 ng. In TLC, the detection limit of AFs was 1 ng. A total of 26 commercially available dried red pepper and 53 feedstuff specimens were analyzed. In Turkey for spices the allowed upper B1 level is 5 ppb and for all foods total AF level is 10 ppb. In dried red peppers, the B1 level higher than 5 ppb was 42.3% and the total AF level greaterthan 10 ppb was 38.4%. In Turkey for mixed feedstuffs the allowed upper total AF level is 50 ppb and in 7.5% of the feedstuffs the total level was higher than 50 ppb.
Keywords: Aflatoxin; Dried red pepper; Feedstuff; HPLC